Resistance to Persuasion: Examining the Influence of Political Ideology on COVID-19 Vaccine Uptake Hesitancy - Brinson, Nancy H. (Frontiers in Communication, 2022)
The COVID-19 pandemic has contributed to the death of over 625,000 Americans and it continues to have monumental consequences worldwide for economic, social and individual life. An effective vaccine program is considered vital to securing collective immunity; yet, many Americans are still hesitant to be vaccinated. This two-part study first experimentally tests two message frames (inoculation vs. control) designed to counter resistance to the COVID-19 vaccine with individuals who are initially supportive, neutral or opposed to it. Based on a key finding from Study 1 (that political ideology appears to be impacting receptiveness to the messaging), Study 2 examines response to these same two messages using either a politicized (Dr. Anthony Fauci) or neutral source to test the mediating effects of political ideology. Results contribute to existing literature by examining inoculation effects in a new context (“debunking” misinformation vs. “prebunking” to bolster supportive attitudes), and demonstrate how psychological reactance is working in tandem with inoculation to influence attitudes toward the COVID-19 vaccine.